Bayes estimators for the reliability and hazard rate functions of Topp-Leone distribution using Type-II censored data. Issue 8 (3rd August 2021) - Arora, Sangeeta; Mahajan, Kalpana K.; Kumari, Ritu
Abstract: The paper develops Bayesian estimators and credible intervals for the reliability function and hazard rate function of Topp-Leone distribution under Type-II censored data by considering informative prior and non-informative prior using symmetric and asymmetric loss functions. Further, Monte Carlo simulation study is carried out to find the Bayes estimates for reliability function and hazard rate along with their credible intervals. Real life data set is also taken up for illustration purpose. Robustness of hyper-parameters is also discussed.